(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Good performance directly contributes to maximizing shareholder value, and serves as a primary driver for attracting new investors. It further demonstrates financial health, effective management, and the potential for future returns. Organizations cannot always operate in the same manner since they are dynamic systems. They must change through several life cycles in order to function smoothly and effectively. One of the main goals for organization across the globe is to improve corporate performance. In order to maximize financial performance and manage financial difficulties, corporate restructuring has evolved into a crucial strategy for businesses. Evidence from literature showed that Organizations encounter challenges which led to financial distress of many and liquidation of many oil and gas companies. Research has shown that not many oil and gas companies have integrated corporate reorganization into their systems for enhancement of their performance. This study therefore examined the effect of corporate reorganization on financial performance of listed oil and gas companies in Nigeria for the period between 2010 - 2024. Ex-post facto research design was used. The population of the study was 14 listed oil and gas companies in Nigeria Using the purposeful sampling techniques, the sample size was 11 listed oil and gas companies The study found that assets restructuring has no significant effect on financial performance as indicated by the coefficient 0.0084 and p-value 0.157 at 5% level of significant while corporate financial restructuring and organizational restructuring have positive and significant effect on financial performance with coefficient (1.3760; 0.1132) and p-value (0.009; 0.003) at 5% level of significant respectively. The study concluded that corporate reorganization enhanced the corporate performance of oil and gas companies. It recommended that Nigerian oil and gas management should create new market strategies, practices, and resources that will boost competitiveness, adapt to market changes, and facilitate the development of unique products and services that will satisfy shifting consumer demand for enhancement and growth of corporate performance.